RECOGNITION OF MARRIAGE AS INVALID LIKE A MEASURE OF RESPONSIBILITY WITHIN FAMILY LAW (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The scientific and practical problems related to the recognition of marriage as invalid like a mean of family and legal responsibility have been analyzed. It has been noted that today there is no single concept of liability in family law within the legal literature. The lack of a single scientific and law-enforcement position regarding the concept, legal nature, purpose, functions, principles, grounds, stages of the application of family and legal responsibility reduces its effectiveness and is negatively reflected in the legal regulation of family relations. This leads to difficulties in interpreting the norms of family law, mistakes in judicial practice, the abuse of law by the direct participants in family legal relations, the destruction of family legal relations.The main result of the study is the conclusion that the recognition of marriage as invalid is a measure of family and legal responsibility for offenses in the form of marriage in violation of the requirements established within the family law of Ukraine. On the basis of the analysis of the norms of the current family law of Ukraine, it has been concluded that the recognition of marriage as invalid like a measure of responsibility within family law should be applied exclusively within the judicial procedure to increase the effectiveness of this measure and the possibility of applying the consequences of marital invalidity. It has been stressed that a person who is underage or incapacitated can not be considered as a subject of a family offense in the form of marriage in violation of the requirements established in the Family Code of Ukraine. A person who knew or ought to have known about obstacles to marriage has the right to apply to the state registration agency of civil status with the application for the annulment of the record of such a marriage or to a court claiming the marriage annulment. If the necessary evidence is available, such an application or claim shall be satisfied. The guilt of the specified person only affects the possibility of applying the consequences of the invalidity of the marriage.